The portrayal of Andromache in Homer and Euripides, "If any woman is unhappy": A play - Κουτσογιάννη, Δήμητρα (Πανεπιστήμιο Πελοποννήσου, 2024)
This Thesis approaches the myth of Andromache, through the lens of the universally acclaimed Euripedean tragedies “Andromache” and The Trojan Women” and of the broadly known Homeric “Iliad”. According to the aforementioned myth, Andromache was married to Hector, who fought in the Trojan War and with whom she had a child. Due to the aftermath of the Trojan War and Hector’s murder, Andromache becomes a commodified victim of slavery. Tragically, the son of Hector’s murderer becomes her abuser. Euripides’s protagonist faces a plethora of challenges, such as child loss, female rivalry, and manipulation. She voices her torment by stating that “If any woman is unhappy, I am”, representing womanhood and the burdens women face regardless of temporal limitations. The Thesis shall commence with thorough research findings on the temporal, spatial, and thematic context of the three plays that bear references to the figure of Andromache. At this point, it is seminal to mention that Iakov (1) defines the Euripidean tragedy as a family drama; thus, it is full of misunderstandings. It is also a political dramatic piece, which addresses the rivalry between Athens and Sparta. It is considered an anti-war manifesto, too, with a connection to the war zone and its consequences. Thus, the myth adopts a multi-faceted profile. In addition, the fruits of the study of a variety of sources will aid the conception of a play that has the ancient myth as its basis. The end product shall be a play based on the myth of the suffering woman and the study material, yet it will be differentiated compared to the original ancient Greek plays. As an example, the structure of the end product is postmodern, containing Acts and Scenes, while the lexis of the postmodern creation complies with current temporal factors. Embedded songs- a modern approach to the ancient “Stasimon”-will support both the plot and its performance. The ethical dimension of the characters of the postmodern dramatic attempt shall not deviate from the ancient approaches. That is to say, although the end product is going to differ in a structural and lexical manner, both the musical and the ethical influences are going to be creatively reproduced. The author of the thesis intends to focus on a postmodern version of Andromache, the symbol of womanhood, motherhood, and female burden. These experiences are timeless, forming, and possibly bitter. (1) See Iakov (1996).
Η Μορφή της Ανδρομάχης στον Όμηρο και τον Ευριπίδη, "Η Πιο Δυστυχισμένη Γυναίκα στον Κόσμο": Θεατρικό Έργο
Keywords: Andromache; Euripides; Illiad; Homer; Trojan war; Trojan women; Ancient Greek drama; Andromache, Euripides, the Iliad, Homer, The Trojan Women, The Trojan War, ancient Greek drama